Development of a Molecular Adjuvant to Enhance Antigen-Specific CD8+ T Cell Responses. Issue 1 (December 2018) - Halbroth, Benedict; Sebastian, Sarah; Poyntz, Hazel C.; Bregu, Migena; Cottingham, Matthew; Hill, Adrian; Spencer, Alexandra
Abstract Despite promising progress in malaria vaccine development, an efficacious subunit vaccine againstP .falciparum remains to be licensed and deployed. This study aimed to improve on the immunogenicity of the leading liver-stage vaccine candidate (ChAd63-MVA ME-TRAP), known to confer protection by eliciting high levels of antigen-specific CD8+ T cells. We previously showed fusion of ME-TRAP to the human MHC class II invariant chain (Ii) could enhance CD8+ T cell responses in non-human primates, but did not progress to clinical testing due to potential risk of auto-immunity by vaccination of humans with a self-antigen. Initial immunogenicity analyses of ME-TRAP fused to subdomains of the Ii showed that the Ii transmembrane domain alone can enhance CD8+ T cell responses. Subsequently, truncated Ii sequences with low homology to human Ii were developed and shown to enhance CD8+ T cell responses. By systematically mutating the TM domain sequence, multimerization of the Ii chain was shown to be important for immune enhancement. We subsequently identified several proteins from a variety of microbial pathogens with similar characteristics, that also enhance the CD8+ T cell response and could therefore be used in viral vector vaccines when potent cell mediated immunity is required.